Premium cigars: Patterns of use, marketings, and health effects - National Academies of Sciences, Engineering, and Medicine; Health and Medicine Division; Board on Population Health and Public Health Practice; Committee on Patterns of Use and Health Effects of Premium Cigars and Priority Research; Aimee M. Mead; Amy B. Geller; Steven M. Teutsch (A consensus study report, 2022)
"The early to mid-1990s saw a large surge in U.S. cigar consumption, including premium cigars. Based on recent import data, premium cigar use may be increasing, though they currently make up a small percent of the total U.S. cigar market. Premium cigars have also been the subject of legal and regulatory efforts for the past decade. In 1998, the National Cancer Institute undertook a comprehensive review of available knowledge about cigars - the only one to date. The resulting research recommendations have largely not been addressed, and many of the identified information gaps persist. Furthermore, there is no single, consistent definition of premium cigars, making research challenging. In response, the Food and Drug Administration (FDA) and the National Institutes of Health commissioned the National Academies of Sciences, Engineering, and Medicine to convene a committee of experts to address this issue. The resulting report, Premium Cig